THE IMPACT OF ASSET STRUCTURE, BUSINESS RISKS AND FIRM SIZE ON PROFITABILITY AND CAPITAL STRUCTURE OF PHARMACEUTICAL SUB-SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE PERIOD 2018-2022 - Chandra, Jennifer; Gwendolin, Gwendolin; Chandra, Teddy; Wijaya, Evelyn (Bilancia : Jurnal Ilmiah Akuntansi, 2024)
This research aims to analyze the effect of Asset Structure, Business Risk, and Firm size on Profitabillity and Capital Structure of pharmaceutical sub-sector companies. In this research, sampling was conducted using purposive sampling method. The samples used in this research were 10 companies out of a total of 12 pharmaceutical sub-sector companies. The data analysis technique used to analyze the data is multiple linear regression analysis. The results showed that asset structure, business risk, and Firm size has insignificant effect on the profitability and capital structure of pharmaceutical sub-sector companies. This research also shows that profitability does not mediate the relationship between asset structure, business risk, Firm size on capital structure. Penelitian ini bertujuan untuk menganalisis pengaruh Struktur Aktiva, Risiko Bisnis, dan Ukuran Perusahaan terhadap Profitabilitas dan Struktur Modal pada perusahaan subsektor farmasi. Dalam penelitian ini pengambilan sampel dilakukan dengan menggunakan metode purposive sampling. Sampel yang digunakan dalam penelitian ini adalah 10 perusahaan dari total 12 perusahaan subsektor farmasi. Teknik analisis data yang digunakan untuk menganalisis data adalah analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa struktur aset, risiko bisnis, dan ukuran perusahaan tidak berpengaruh signifikan terhadap profitabilitas dan struktur modal pada perusahaan subsektor farmasi. Penelitian ini juga menunjukkan bahwa profitabilitas tidak memediasi hubungan antara struktur aset, risiko bisnis, ukuran perusahaan terhadap struktur modal.